John Constantine, Hellblazer. Volume 11, Last man standing - Jenkins, Paul, 1965- (DC Comics/Vertigo, 2015)
"In this new Hellblazer collection, John Constantine, while scouting for blackmail victims at an orgy, John finds himself accidentally summoning up sinister beings known as the Mendw, with terrible consequences for an anorexic girl and her abusive father. Plus, cattle mutiliations in Yorkshire hold no interest for Constantine until a nosy tabloid reporter chases him out of London. Once in the country, John discovers that one of the villagers is transforming into a werewolf, but this strange case of lycanthropy is only a portent of worse things to come.."--